The Glymphatic System: A Review - Oliveira, Louise Makarem; Figueiredo, Eberval Gadelha; Peres, Carlos Michel Albuquerque (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
The brain represents ∼ 2% of the adult body mass; conversely, it is responsible for 20% to 25% of the glucose and 20% of the oxygen consumption, receiving 15% of the cardiac output. This substantial metabolic rate is associated with a significant production of biological debris, which is potentially toxic. Therefore, a complex and efficient clearance system is required to prevent the accumulation of byproducts and ensure optimal function. However, until today, there is little knowledge about this topic. The glymphatic system, also known as perivascular pathway, is a recently described glial-dependent network that is responsible for the clearance of metabolites from the central nervous system (CNS), playing a role equivalent to the one played by the lymphatic vessels present in other organs. Studies have demonstrated that the glymphatic pathway has a paramount role in protein homeostasis, and that the malfunction of this system may be related to the development of neurodegenerative disorders such as Alzheimer disease and normal pressure hydrocephalus. They also showed that body posture, exercise and the state of consciousness influence the glymphatic transport. In this context, the understanding of this clearance system could not only clarify the pathophysiology of several diseases, but also contribute to future therapeutic interventions. In the present article, we will evaluate the glymphatic pathway, focusing on the factors that regulate its flow, as well as on its role in CNS physiology and in disease initiation and progression, including dementia, hydrocephalus, glaucoma and traumatic brain injury. Ultimately, this review also aims to encourage further research on novel therapeutic targets.
Keywords: glymphatic system; metabolite clearance; central nervous system; brain metabolism